1 COVID-19 and QTc: is hydroxychloroquine worth the risk? A review of QT prolongation in hospitalised COVID-19 patients treated with hydroxychloroquine and azithromycin. (30th September 2020) - Pollock, A; Kumar, R; Devitt, P; Kent, B; Daly, C
Abstract : Background: Hydroxychloroquine (HC) and Azithromycin (AZ) is a novel treatment regimen in the management of Coronavirus disease 2019 (COVID-19). Both HC and AZ are associated with QT prolongation, which can precede malignant arrhythmias such as torsade de pointes (TdP) and ventricular fibrillation. Limited literature exists to establish the incidence of QT prolongation with COVID-19 treatment and its relationship with morbidity and mortality. This study was performed to assess the incidence of QT prolongation secondary to HC and AZ, and how it related to morbidity and mortality. Methods: A retrospective chart review was performed of COVID-19 patients treated with HC, with or without concomitant AZ, in our hospital in March and April 2020. Their baseline demographic characteristics and co-morbidities were recorded. The baseline corrected QT interval (QTc) and change in QTc was calculated using Bazett's formula on both electrocardiograms (ECGs) and inpatient cardiac monitors. Results: Out of 62 PCR confirmed COVID-19 patients (34% female; mean age 67), 58 patients (93.5%) received both HC and AZ, while 4 patients (6.5%) received HC alone. Hypertension was the most common co-morbidity (33.5%) followed by diabetes mellitus (16%), known ischaemic heart disease (19.4%) and atrial fibrillation (8%). Twenty-three patients (37.1%) were on ≥2 additional QT prolonging medications. Mean baseline QTc was 445.7 msec (SD 30.4). The mean QT peak was 469.3 msec (SD 44.5) with a mean change in QTc of 28.4 msec (SD 31.4). QT prolongation was seen in 62.9% of patients, with increase in QTc ≥60 msec or QT peak ≥500 msec in 24.2% of patients. The mean length of stay was 19.7 days (SD 15.2) (range 3–57 days). Treatment was stopped in 6 patients (9.7%) due to QT prolongation. There were no cases of torsade de pointes (TdP). Mortality was 22.6%, with 16.1% of patients admitted to an intensive care unit (ICU). Patients with QT prolongation had a significantly higher risk of death (33% vs 4.3%), with an increased likelihood of ICU admission (20.5% vs 8.7%), and increased length of stay (24.7 days vs 18.6 days). Conclusions: In this study, patients who were treated with HC and AZ were at high risk of QT prolongation. QT prolongation was associated with higher mortality, increased ICU admission and longer length of stay. Close cardiac monitoring and rationalisation of additional QT prolonging drugs are essential to prevent adverse cardiac events with this treatment regimen.